Pengaruh Persepsi Kebermanfaatan, Persepsi Kemudahan Penggunaan, Dan Tingkat Sosialisasi E-Samsat Terhadap Penerimaan Masyarakat Menggunakan E-Samsat (Studi Empiris Masyarakat Kota Denpasar) - Ni Putu Mahindu Pradnya Utami; Putu Sukma Kurniawan (Universitas Pendidikan Ganesha, 2020)
This study was conducted with the aim to determine the effect of perceived usefulness, perceived ease of use, and level of socialixation pf E-SAMSAT on community acceptance using E-SAMSAT, especially people who live in Denpasar City. This type of research includes quantitative research, where the data used in this study are primary data, collected through the distribution of questionnaires directly and through Google forms to respondents. The population ini the study were motor vechile taxpayers registered using E-SAMSAT ath the Samsat Office in Denpasar city. The number registered in 2019 was 12,261 taxpayers. Samples were selected by purposive sampling technique, the number of samples obtained by looking at Isaac and Michael tables with an error rate of 5% so that the samples obtained were 336 respondents. Data analysis techniques consisted of data quality tests, descriptive analyzes, classic assumption tests, multiple linear regression analysis, t tests, and the coefficient of determination (R2) test with the help of SPSS version 20.0 for windows. The results of this study indicate that each perceived usefulness variable (X1), perceived ease of use (X2) variable, and the level of E-SAMSAT socialization level (X3) have a positive and significant effect on community acceptance using E-SAMSAT (Y)